2007
DOI: 10.1590/s1516-31802007000200010
|View full text |Cite
|
Sign up to set email alerts
|

The role of physician counseling in improving adherence to physical activity among the general population

Abstract: The regular practice of physical activity at appropriate levels ensures various benefi ts for the individual over the short, medium and long terms. It is therefore important in health promotion. On the other hand, sedentary behavior has reached alarming levels among the general population, which qualifi es it as a serious health problem of endemic proportions. The present review describes public health problems consequent to sedentary behavior and the importance of physician counseling for change their patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 60 publications
(47 reference statements)
0
15
0
14
Order By: Relevance
“…As has already been seen that those physicians who were active themselves tend to promote physical activity in their patients also. [23][24][25] Further, the medical curriculum needs to be modified to stress more on health promotion and healthy lifestyle rather than merely concentrating on treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As has already been seen that those physicians who were active themselves tend to promote physical activity in their patients also. [23][24][25] Further, the medical curriculum needs to be modified to stress more on health promotion and healthy lifestyle rather than merely concentrating on treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…4 concluded that early treatment with dexamethasone reduced the seven-day mortality among septic shock patients and showed a trend towards reduction of 28-day mortality. Ribeiro et al 5 hope to suggest methodologies that will enable physicians to promote regular physical activity at appropriate levels, ensuring various benefits for the individual over the short, medium and long terms, which determines their importance in the promotion of health. On the other hand, sedentary behavior has reached alarming levels among the general population, which qualifies it as a serious health problem of endemic proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de reconhecidos os benefícios de uma alimentação adequada e saudável, rica em alimentos in natura e minimamente processados, e com reduzida quantidade de alimentos processados e ultraprocessados 2, bem como da prática regular de atividade física para a promoção da saúde, prevenção e controle das DCNT 3 , a maioria dos brasileiros relata baixa adesão a modos saudáveis de vida 4 . Este cenário aponta para a necessidade da ampliação da prática do aconselhamento sobre estes aspectos nos serviços de saúde 5,6 . O aconselhamento em saúde é compreendido como um processo genérico de ajuda, envolve desde orientações individuais ou coletivas até estratégias de intervenção.…”
Section: Introductionunclassified
“…O aconselhamento em saúde é compreendido como um processo genérico de ajuda, envolve desde orientações individuais ou coletivas até estratégias de intervenção. Ele pressupõe a construção de ações de educação em saúde pelo profissional com vistas à construção de modos saudáveis de viver 5,6 . Neste contexto, os serviços de Atenção Primária à Saúde (APS), por serem espaços legítimos de construção e implementação de ações assistenciais, preventivas e de promoção da saúde, de forma integral e segundo a realidade do indivíduo, são locais privilegiados para o seu desenvolvimento 7 .…”
Section: Introductionunclassified